2021
DOI: 10.3389/fpubh.2021.802180
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Psychosocial Well-Being During Pandemic-Associated Pre-deployment Quarantine

Abstract: Background: With the purpose of preventing SARS-Cov-2 traveling with the troops, pre-deployment and post-deployment quarantine are mandatory for the German military. This study investigates which factors could be addressed in order to facilitate adherence and mental health during isolation.Method: Six hundred three soldiers completed questionnaires at the beginning and at the end of pre-deployment quarantine: Mini-SCL (BSI), Perceived Social Support (FSozU-K22), Unit Cohesion, Military Quarantine Adherence Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The only two studies, to our knowledge, studying military mental health associated with deployment-related quarantining have not found indications for higher incidence or prevalence rates of mental disorders following quarantining (35,36), although a considerable percentage of sleeping problems was reported (32%) in one study (35,37), which is often a precursor for mental health disorders (38)(39)(40)(41). At the same time, differing trajectories of more vulnerable groups might be masked, when only statistic differences in means are explored (25,26).…”
Section: Impact Of Quarantining On Psychosocial Wellbeingmentioning
confidence: 86%
See 2 more Smart Citations
“…The only two studies, to our knowledge, studying military mental health associated with deployment-related quarantining have not found indications for higher incidence or prevalence rates of mental disorders following quarantining (35,36), although a considerable percentage of sleeping problems was reported (32%) in one study (35,37), which is often a precursor for mental health disorders (38)(39)(40)(41). At the same time, differing trajectories of more vulnerable groups might be masked, when only statistic differences in means are explored (25,26).…”
Section: Impact Of Quarantining On Psychosocial Wellbeingmentioning
confidence: 86%
“…Seven factors yielded satisfactory to good reliability (consistency; 0.73 ≤ α ≤ 0.83), while the two most heterogeneous scales, namely, "fulfilled need for intimacy/bonding" and "clear communication of the quarantine protocol" (α ≤ 0.58), had to be z-standardized to reach satisfactory consistency (α > 0.7): For consistency reasons, all items were z-standardized before calculating scale means. More details on the scales and their validation have been reported previously (36,59).…”
Section: Quarantine-associated Risk and Resilience Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manageability of the pandemic situation in many hospitals in Germany, but especially in the Bundeswehr hospitals, may have contributed to these results. Hierarchical structures in the military and a military-specific unit cohesion also might have positive effects on coping strategies and resilience ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In developing their health communication strategy, organizations like the military should consider the role of leaders, unit climate and individual differences in beliefs about health [ 34 ]. Recent studies have found that individual differences, such as trait reactance, perceived injunctive norms, and COVID-19 conspiracy beliefs, are associated with lower likelihood of engaging in preventive health behaviors [ 34 37 ]. While providing individuals with clear rules and accurate information is valuable, public-health messaging driven by data alone risks neglecting how health beliefs factor into health behaviors.…”
Section: Discussionmentioning
confidence: 99%